Rubidium detected with X-ray fluorescence spectrometry: A new semi-quantitative assessment of clay content in sedimentary rocks - Ramasamy, Nagarajan; Kessler, L. (Geological Society of Malaysia, 2013)
This paper deals with assessment of clay content in sedimentary rocks using portable X-ray fluorescence spectrometry. Whilst measuring trace metal content of sedimentary rocks, it was noted a positive, quasi-linear correlation existed between the rock's Rb concentration and both percentage of clay fraction, and also natural gamma ray radioactivity. Rb is relatively easy to measure with XRF and provides a semi-quantitative assessment of clay content. The measurement error of the tool is less than 10 %. Initial data indicate that the Rubidium content varies slightly in respect to clay mineral composition, given some samples deviate from others, by showing higher or lower-than-expected values. In clastic sediments, the Rb-XRF method can be used as an alternative to Gamma-Ray in determining clay content, such as to describe the cleanness of sand or carbonate. For industrial limestone mining, the XRF tool could be used to estimate cleanness of carbonates, hence rock strength. It is believed that XRF Rubidium measurements could also be carried out in the subsurface.